Economic status and acknowledgement of earned entitlement - Barr, Abigail; Burns, Justine; Miller, Luis; Shaw, Ingrid (Elsevier, 2015)
We present a series of experiments that investigates whether tendencies to acknowledge entitlement owing to effort and productivity are associated with within society economic status. Each participant played a four-person dictator game under one of two treatments, under one initial endowments were earned, under the other they were randomly assigned. The experiments were conducted in the United Kingdom, and South Africa. In both locations we found that relatively well-off individuals make allocations to others that reflect those others’ initial endowments more when those endowments were earned rather than random; among relatively poor individuals this was not the case.